DEVELOPING SPEAKING SKILLS IN ENGLISH LEARNERS - Jumaboyeva Oʻgʻiloy Yaxshilik qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Speaking skills are a fundamental component of language proficiency and play a crucial role in effective communication. Developing speaking abilities in English learners remains a challenge due to anxiety, lack of practice, and limited exposure to authentic communication. This article examines strategies and methods for enhancing speaking skills among English learners, including communicative activities, role-plays, games,  and  collaborative  tasks.  The  study  highlights  the  importance  of  teacher guidance,  learner  motivation,  and  interactive  classroom  environments.  Findings indicate  that  consistent  practice,  feedback,  and  learner-centered  approaches significantly improve speaking proficiency (Harmer, 2007; Thornbury, 2005).